Incidence and factors associated with cutaneous immune-related adverse events to immune check point inhibitors: An ambispective cohort study - Luangnara, Athitaya; Kiratikanon, Salin; Ketpueak, Thanika; Suksombooncharoen, Thatthan; Charoentum, Chaiyut; Chewaskulyong, Busyamas; Tovanabutra, Napatra; Chiewchanvit, Siri; Nochaiwong, Surapon; Chuamanochan, Mati (Frontiers in Immunology, 2022)
Background Although immune checkpoint inhibitors (ICIs) have become the frontline treatment option for patients with various advanced cancers due to improved survival, they can be associated with a spectrum of cutaneous immune-related adverse events (cirAEs). However, little is known regarding the occurrence and patterns of cirAE-related ICI therapy in patients of different races other than white populations. Therefore, we investigated the incidence and associated factors of cirAEs among cancer patients in northern Thailand. Methods A referral-center-based ambispective cohort study was conducted from January 1, 2017, to March 31, 2021. Based on a linked database and merged patient-level data, adult patients with pathologically confirmed cancer who were diagnosed and received ICI therapy regardless of cancer type and followed up through August 31, 2021, were included. All cirAE-related ICI therapy was based on clinical evaluation and ascertainment by a board-certified dermatologist. The incidence of cirAE-related ICI therapy with confidence intervals (CIs) across cancer- and ICI therapy-specific groups was estimated. Factors associated with cirAEs were evaluated using multivariable modified Poisson regression to estimate risk ratios (RRs) and 95% CIs. Results The study included 112 patients (67 men [59.8%]; mean age, 65.0 [range, 31.0-88.0] years), who were mainly diagnosed with lung cancer (56.3%), followed by liver cancer (19.6%). The overall incidence of cirAE-related ICI therapy was 32.1% (95% CI, 24.1-41.4); however, there was no substantial difference in sex, cancer type, or individual ICI therapy. The two identified prognostic risk factors of cirAE-related ICI therapy were age >75 years (adjusted RR, 2.13; 95% CI, 1.09-4.15; P=0.027) and pre-existing chronic kidney disease stages 3-4 (adjusted RR, 3.52; 95% CI, 2.33-5.31; P<0.001). Conclusions The incidence of cirAE-related ICI therapy among Thai cancer patients was comparable to that in white populations. Early identification, particularly in elderly patients and those with CKD, should be implemented in clinical practice to help optimize therapeutic decision-making and patient health outcomes.